The Contribution of Caritas in Veritate towards the Humanisation of Niger-Delta and Its Environs (Hekima Review, 2015)
The technological advancement of our contemporary world has brought significant improvements to humanity. In the Niger Delta of Nigeria however, common and expertise knowledge reveal that slowly and steadily, technological use can be counter-productive. This is typied by the unabated use of gas aring technology in oil extraction for government revenue generation, which has not only degraded this region and its envi-rons but has also occasioned convict in the area. The Catholic Church has produced relevant documents; among them is Caritas in Veritate (CV), which while inviting all men and women of good-will to be cautious, proposes respect for God that avoids predatory engagements with the earth and its resources in pursuit of economic development. Hence, I reflect on how CV has paradigmatically inspired the Catholic Bishops of Nigeria to exercise their prophetic mandate in contributing towards the humanisation of Niger-Delta & its environs.